Play-based interventions for mental health: A systematic review and meta-analysis focused on children and adolescents with autism spectrum disorder and developmental language disorder. (February 2022) - Francis, Gill; Deniz, Emre; Torgerson, Carole; Toseeb, Umar
Background and aims: Play-based interventions are used ubiquitously with children with social, communication, and language needs but the impact of these interventions on the mental health of this group of children is unknown. Despite their pre-existing challenges, the mental health of children with developmental language disorder (DLD) and autism spectrum disorder (ASD) should be given equal consideration to the other more salient features of their condition. To this aim, a systematic literature review with meta-analysis was undertaken to assess the impact of play-based interventions on mental health outcomes from studies of children with DLD and ASD, as well as to identify the characteristics of research in this field. Methods: The study used full systematic review design reported to the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) guidelines (PRISMA prisma-statement.org) with pre-specified inclusion criteria and explicit, transparent and replicable methods at each stage of the review. The study selection process involved a rigorous systematic search of seven academic databases, double screening of abstracts, and full-text screening to identify studies using randomised controlled trial (RCT) and quasi-experimental (QE) designs to assess mental health outcomes from interventions supporting children with DLD and ASD. For reliability, data extraction of included studies, as well as risk of bias assessments were conducted by two study authors. Qualitative data were synthesised narratively and quantified data were used in the metaanalytic calculation. Main contribution: A total of 2, 882 papers were identified from the literature search which were double screened at the abstract (n  =  1, 785) and full-text (n  =  366) levels resulting in 10 papers meeting the criteria for inclusion in the review. There were 8 RCTs and 2 QEs using 7 named play-based interventions with ASD participants only. Meta-analysis of 5 studies addressing positive mental health outcomes (e.g. positive affect and emotional functioning) found a significant overall intervention effect (Cohen's d = 1.60 (95% CI [0.37, 2.82], p = 0.01); meta-analysis of 6 studies addressing negative mental health outcomes (e.g., negative affect, internalising and externalising problems) found a non-significant overall intervention effect (Cohen's d = 0.04 -0.17 (95% CI [-0.04, 0.51], p = 0.88). Conclusions: A key observation is the diversity of study characteristics relating to study sample size, duration of interventions, study settings, background of interventionists, and variability of specific mental health outcomes. Play-based interventions appear to have a beneficial effect on positive, but not negative, mental health in children with ASD. There are no high quality studies investigating the efficacy of such interventions in children with DLD. Implications: This review provides good evidence of the need for further research into how commonly used play-based interventions designed to support the social, communication, and language needs of young people may impact the mental health of children with ASD or DLD.